PERKEMBANGAN FUNGSI PENGGUNAAN BAHASA PADA ANAK USIA 5 TAHUN (Studi Kasus pada Azza Aqila Jihan Syuasabitha) - Ali Kusno (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
5 years old kid is the golden age of sensitive periods. One that developed was the pragmatic function of the language used. The development of these functions is in line with their physical, mental, intellectual, and social development. This research is related to the development of children's language function, with case examples to Azza Aqila Jihan Syuasabitha (Jihan). Data collection in this study is used observation techniques. The subject of this study is the author's own child. This study aims to describe the development of Jihan's speech as a child that is 5 year old based on the grouping of language functions according to M.A.K Halliday. The results showed that the child was able to apply the overall function of language used that is instrumental, regulatory/dogmatic, interactional, personal, heuristic, imaginative, and representational. The function of language use that is the most rapidly growing is function imaginative. The achievement is influenced by biological factors (parents who have good language skills) and social environment (at home, school and others).